PERLINDUNGAN HUKUM TERHADAP HAK CIPTA LAGU DAN MUSIK MENURUT UNDANG-UNDANG NOMOR 28 TAHUN 2004 - UTAMA, ARYA; TITAWATI, TITIN; LOILEWEN, ALINE FEBRYANI (GANEC SWARA, 2019)
The rapid development of information technology has a positive and negative impact on the enforcement of Copyright law. The positive impact is in line with technological advances, especially the internet, so it's easy to buy original songs or music through online shopping facilities. While the negative impact is the increasing number of links downloading songs or illegal music in cyberspace, as well as the easier the piracy of voice recording works in the real world.     The research method used in this study is a library research method that is normative juridical, namely research that refers to legal norms that exist in legislation, literature, expert opinions, papers, etc. In this case the copyright registration of the song and music is not an evidence if there is a copyright dispute over the song and music on the internet media, if there is prior publication carried out by one of the parties to the dispute then someone who can prove the authenticity of his creation will be the copyright holder of the disputed song or music. In Article 35 paragraph (4) the Copyright Act explains that the provisions on registration of work are not an obligation to obtain a Copyright, because Copyright protection arises automatically, (Automatic Protection) since the creation is manifested in a tangible form, without having to go through registration procedure